KNOWING HOSPITALIZATION IN PEDIATRIC ICU UNDER THE HEALTH AND FAMILY (CIPEEX, 2022)
INTRODUCTION: THE TERM HOSPITALIZATION BRINGS IN ITS ESSENCE THE PERCEPTION OF AN UNPLEASANT SITUATION RESULTING IN LOSSES, REGARDLESS OF WHETHER OR NOT A SHORT PERIOD OF TIME OR IN WHICH AGE GROUP THE PATIENT IS (MORAIS; COSTA, 2009). FOR THE FAMILY TO COPE WITH THE SITUATION OF AN ILLNESS MAINLY OF A CHILD, IT IS FOR THE PARENTS A FEELING THAT SHOULD NOT BE OVERLOOKED BY THE CARE OF THE NURSING TEAM, BECAUSE IF SUCH A SITUATION WHEN UNACCOMPANIED AND SUPPORTED BY PROFESSIONALS, IT ALSO TRIGGERS A FAMILY CRISIS , WHERE IN FRONT OF THE PAIN THE PARENTS EXPERIENCE SEVERAL FEELINGS, BEING THE GUILT AND IMPOTENCE IN THE EAGERNESS TO PROTECT THE CHILD WHAT IS MORE AND TAKEN INTO ACCOUNT (HAYKAWA; MARCON; HIGARASHI, 2009) OBJECTIVE: TO KNOW BEFORE THE SCIENTIFIC LITERATURE AS DESCRIBED IN THE PEDIATRIC ICU. METHODOLOGY: THIS STUDY WAS A DESCRIPTIVE RESEARCH OF QUALITATIVE ANALYSIS IN AN INTEGRATIVE LITERATURE REVIEW FORMAT (MENDES; SILVERA; GALVƑO, 2008). THE SEARCH FOR ARTICLES IN THE VIRTUAL HEALTH DATABASES IN THE VIRTUAL HEALTH LIBRARY (VHL) LATIN AMERICAN AND CARIBBEAN LITERATURE ON HEALTH SCIENCES (LILACS) THE ONLINE SYSTEM OF SEARCH AND ANALYSIS OF MEDICAL LITERATURE (MEDLINE) AND THE ELECTRONIC SCIENTIFIC LIBRARY (SCIELO), THE SAMPLE AND COMPOSED OF 9 ARTICLES BETWEEN THE YEARS 2007 TO 2017, WITH THE DESCRIPTORS: NURSING, UTI PEDIATRIC, HOSPITALIZATION. RESULTS: THREE CATEGORIES WERE CONSIDERED: FEELINGS EXPRESSED BY FAMILY MEMBERS AND NURSING TEAM; SPECIALIZED ENVIRONMENT; VISION UNDER HUMANIZED CARE ASPECT. FINAL CONSIDERATIONS: WHEN CHOOSING TO WORK IN UTI PEDIATRIC IT IS IMPORTANT THAT THE NURSING PROFESSIONAL IS AWARE OF THE UNFOLDING OF THEIR FUNCTIONS, WHICH INTERCONNECT NOT ONLY WITH THE TECHNICAL DETERIORATION OF THE PROFESSION, BUT ALSO WITH EMOTIONAL EXHAUSTION. THE FUNCTIONS OF THE HEALTH TEAM THAT ATTEND THE PEDIATRIC UTI ARE CONSTANTLY RELATED TO THE STRUGGLE FOR SURVIVAL, WHICH IN MANY CASES PATIENTS COME TO DEATH, BRINGING FEELINGS OF VULNERABILITY NOT ONLY FROM THE FAMILY, BUT ALSO FROM THOSE WHO EVEN IN A PROFESSIONAL WAY, INVOLVED IN THE CASES SERVED, HOPING FOR OVERCOMING THE PATIENT AND THE COMFORT OF THE FAMILY.
Keywords: Nursing. Pediatric ICU. Humanization. Family